ANALISIS TANGGUNG JAWAB GURU BIDANG STUDI AQIDAH AKHLAK DALAM MELAKSANAKAN PEMBELAJARAN SAAT PANDEMI COVID-19 DI MTsN 5 PIDIE - Nurbayani; Safrina Ariani; Muhammad Hanif (FITRAH: International Islamic Education Journal, 2022)
The implementation of learning during the Covid-19 period has undergone a fundamental change from face-to-face learning to a bold learning system. This certainly affects the teacher's responsibility in carrying out these learning activities, including the Aqidah Akhlak subject teacher at MTsN 5 Pidie. The purpose of this study was to find out the responsibilities of moral aqidah teachers in implementing learning during the Covid-19 pandemic at MTsN 5 Pidie, implementing the responsibilities of moral aqidah teachers in carrying out learning during the Covid-19 period and teacher obstacles in implementing the responsibilities of learning moral aqidah during the Covid-19 period. at MTs N 5 Pidie. This study uses a descriptive approach and type of research. The subjects of this study consisted of Aqidah Ahklak teachers and students. Data collection techniques were carried out by observation, interviews, questionnaires and documentation. Based on the results of the study, it can be seen that the form of responsibility of the Aqidah Akhlak teacher during the Covid-19 period at MTsN 5 Pidie is to increase student interest and perseverance in learning, complete professional assignments, motivate students to be active and enthusiastic about learning, carry out activities according to a predetermined schedule and learning outcomes. students at MTsN 5 Pidie. The implementation of teacher responsibilities in learning Aqidah Akhlak during the Covid-19 period at MTs N 5 Pidie provides motivation and encouragement for student learning during Covid-19, carries out learning activities according to the provisions of the Ministry of Education and Culture, shapes students' personalities in accordance with Islam, provides guidance and fostering the morals of students, both the morals of Allah SWT, the morals of fellow human beings and the morals of the surrounding environment. The teacher's obstacles in implementing the Aqidah Akhlak learning responsibilities during the Covid-19 period at MTs N 5 Pidie are limited learning facilities, the level of knowledge of Aqidah Akhlak teachers and students who are still minimal regarding learning applications, the difficulty of teachers in controlling students during learning and obstacles in evaluating evaluations.